2012
DOI: 10.1093/brain/aws061
|View full text |Cite
|
Sign up to set email alerts
|

Dynamin 2 mutations in Charcot–Marie–Tooth neuropathy highlight the importance of clathrin-mediated endocytosis in myelination

Abstract: Mutations in dynamin 2 (DNM2) lead to dominant intermediate Charcot-Marie-Tooth neuropathy type B, while a different set of DNM2 mutations cause autosomal dominant centronuclear myopathy. In this study, we aimed to elucidate the disease mechanisms in dominant intermediate Charcot-Marie-Tooth neuropathy type B and to find explanations for the tissue-specific defects that are associated with different DNM2 mutations in dominant intermediate Charcot-Marie-Tooth neuropathy type B versus autosomal dominant centronu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 44 publications
2
65
0
Order By: Relevance
“…Our study along with several other reports emphasizes that DNM2 has a key role in endocytosis, and that disease-causing mutations impact on this function. 9,[21][22][23] We speculate that alterations in endocytosis during development could explain the pleiotropic phenotype observed in patients with this congenital syndrome. (d) The p.Phe379Val protein exhibits B20% lower GTPase activity using a malachite green-based assay (P-value *0.05 for three independent experiments using the Student's t-test).…”
Section: Discussionmentioning
confidence: 93%
“…Our study along with several other reports emphasizes that DNM2 has a key role in endocytosis, and that disease-causing mutations impact on this function. 9,[21][22][23] We speculate that alterations in endocytosis during development could explain the pleiotropic phenotype observed in patients with this congenital syndrome. (d) The p.Phe379Val protein exhibits B20% lower GTPase activity using a malachite green-based assay (P-value *0.05 for three independent experiments using the Student's t-test).…”
Section: Discussionmentioning
confidence: 93%
“…PIPKIγ phosphorylates phosphatidylinositol 4-phosphate to generate phosphatidylinositol-4,5-bisphosphate (PIP 2 ) and the localized synthesis of PIP 2 is important for asymmetric process retraction during directional Schwann cell migration (Gatto et al, 2007). Dynamin 2 is involved in clathrin-mediated endocytosis and required for Schwann cell myelination (Sidiropoulos et al, 2012), CNTNAP1 is an essential component of Ranvier domains, while knockdown of ADCY6 orthologues in zebrafish blocked PNS myelination (Laquérriere et al, 2014). GLE1 function has not been associated with PNS myelination, however RNA expression profiling of spinal cord from LCCS1 fetuses indicated that oligodendrocyte dysfunction may be a factor in disease pathogenesis (Pakkasjarvi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The CMT-neuropathy related mutation G358R 16,17 is located in the C-terminus of L1N S (Extended Data Fig. 3c).…”
mentioning
confidence: 99%